Numerical investigation and recurrence plot analysis of pulsating magnetohydrodynamic mixed convection over a backward facing step - Selimefendigil, Fatih (Nonlinear Analysis: Modelling and Control, 2015)
In the current study, numerical investigation of pulsating magnetohydrodynamic mixed convection over a backward facing step is carried out for the range of parameters; Reynolds number (25 ⩽ Re ⩽ 100), Hartmann number (0 ⩽ Ha ⩽ 60), Strouhal number (0.1 ⩽ St ⩽ 1) and Gr number is kept at Gr = 104. The governing equations are solved with a general purpose finite element based solver. The effects of various parameters on the fluid flow and heat transfer characteristics are numerically studied. It is observed that the flow field and heat transfer rate are influenced by the variations of Reynolds, Hartmann and Strouhal numbers. Furthermore, recurrence plot analysis is applied for the analysis of the time series (spatial averaged Nusselt number along the bottom wall downstream of the step) and for a combination of different parameters, the systems are identified using recurrence quantification analysis parameters including recurrence rate, laminarity, determinism, trapping time and entropy.
Keywords: backward facing step; MHD flow; recurrence quantification analysis; nonlinear time series